2019
DOI: 10.1186/s10194-019-1026-8
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations of sensorimotor processing in migraine: a controlled longitudinal study of beta event related desynchronization

Abstract: Background: The migraine brain seems to undergo cyclic fluctuations of sensory processing. For instance, during the preictal phase, migraineurs experience symptoms and signs of altered pain perception as well as other wellknown premonitory CNS-symptoms. In the present study we measured EEG-activation to non-painful motor and sensorimotor tasks in the different phases of the migraine cycle by longitudinal measurements of beta event related desynchronization (beta-ERD). Methods: We recorded electroencephalograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 64 publications
2
19
0
Order By: Relevance
“…There are two complementary pathways related to pain processing: the medial and lateral pain pathways 33 . In the present study, ONFH patients showed functional decline in the primary sensory cortex, which is compatible with the existence of complementary pathway related to pain processing and align with the results of brain function studies in other non-central nervous system diseases with pain 34,35 . Interestingly, both of these pathways involve the insular cortex.…”
Section: Discussionsupporting
confidence: 91%
“…There are two complementary pathways related to pain processing: the medial and lateral pain pathways 33 . In the present study, ONFH patients showed functional decline in the primary sensory cortex, which is compatible with the existence of complementary pathway related to pain processing and align with the results of brain function studies in other non-central nervous system diseases with pain 34,35 . Interestingly, both of these pathways involve the insular cortex.…”
Section: Discussionsupporting
confidence: 91%
“…However, Wang [8] and Zhao [24] et al reported opposite resting-state neural activity of the bilateral PoCG in migraineurs with all headache subphases by low-frequency oscillations and regional homogeneity approaches to reflect the spontaneous neural function of the brain. In addition, an electroencephalography-related study [25] demonstrated higher desynchronization and power overlying the primary sensorimotor cortex in the preictal phase compared to the interictal phase, with no significant differences between interictal migraineurs and HCs. The heterogeneity of the migraineurs phase and the use of different neuroimaging methods might explain the discrepancy between the studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, Wang [8] and Zhao [24] et al reported opposite resting-state neural activity of the bilateral PoCG in migraineurs with all headache subphases by low-frequency oscillations and regional homogeneity approaches to re ect the spontaneous neural function of the brain. In addition, an electroencephalography-related study [25] demonstrated higher desynchronization and power overlying the primary sensorimotor cortex in the preictal phase compared to the interictal phase, with no signi cant differences between interictal migraineurs and HCs. The heterogeneity of the migraineurs phase and the use of different neuroimaging methods might explain the discrepancy between the studies.…”
Section: Discussionmentioning
confidence: 99%